Nonalcoholic Fatty Liver Disease in Canadian First Nations and Non-First Nations Patients. (28th April 2016) - Uhanova, Julia; Minuk, Gerald; Lopez Ficher, Federico; Chandok, Natasha
Abstract : Background. Features of nonalcoholic fatty liver disease (NAFLD) have yet to be described in the Canadian First Nations (FN) population. The aim of this study was to compare the prevalence, severity, and outcome of NAFLD in FN versus non-FN patients at an urban, tertiary care centre. Methods. Adults with NAFLD and no additional liver disease were identified in a prospectively derived database at the University of Manitoba. Demographic, clinical, laboratory, imaging, and histologic data were analyzed. Results. 482 subjects fulfilled diagnostic criteria for NAFLD, including 33 (7%) FN. Aside from rural residence, diabetes and cholestasis being more common in FN patients, the ages, gender distributions, clinical and radiologic features, and liver enzyme/function test results were similar in the two cohorts. Noninvasive tests of fibrosis (APRI and NAFLD fibrosis scores) were also similar in the two cohorts. There were no significant differences in liver enzyme or function tests in either cohort after approximately three years of follow-up. Conclusion. Compared to the prevalence of FN persons in the general population of this study site (10–15%), FN patients were underrepresented in this NAFLD population. The severity and progression of liver disease in FN patients appear to be similar to those in non-FN patients.